Coulomb Three-Body Effects in the Single Ionization of Helium by 16MeV $O^{7+}$ Impact (Journal of Atomic and Molecular Sciences, 2016)
Three-Coulomb-wave (3C) model is applied to study the single ionization ofhelium by 16MeV $O^{7+}$ impact in the scattering plane. Fully differential cross sections(FDCS) is presented for the different momentum transfers. Our theoretical results arecompared with the recent experimental data and the results of continuum distorted-waveeikonal-initial-state (CDW-EIS). It is shown that the 3C calculations qualitativelyreproduce the experimental peak structure, especially at smaller momentum transfers.
Keywords: Three-Coulomb-wave; single ionization; fully differential cross section.